2002
DOI: 10.1046/j.1365-2672.2002.01506.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of root mat associated Agrobacterium strains from plant material and other sample types by post-enrichment TaqMan PCR

Abstract: Aims: The development of a¯uorogenic, 5¢ nuclease, TaqMan PCR assay for the detection of Ri-plasmids from root mat inducing Agrobacterium biovar 1 strains. Methods and Results: A TaqMan probe and primer set were designed within the T-DNA sequence of a known root mat inducing Agrobacterium strain. One hundred and ten Agrobacterium and closely related bacteria were tested using this novel PCR and compared with results from a conventional PCR which detects Ti and Ri-plasmids. The Agrobacterium selective media, Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 19 publications
0
25
0
1
Order By: Relevance
“…Real-time quantitative PCR (RTQ-PCR) has been shown to be a powerful tool for quantifying bacterial abundance in many different kinds of complex environmental samples down to the genus and species levels (3,17,44,48). In recent studies, the abundance of a genus or species in an environmental sample has also been related to the overall eubacterial abundance in the analyzed system (1,5,32,42).…”
mentioning
confidence: 99%
“…Real-time quantitative PCR (RTQ-PCR) has been shown to be a powerful tool for quantifying bacterial abundance in many different kinds of complex environmental samples down to the genus and species levels (3,17,44,48). In recent studies, the abundance of a genus or species in an environmental sample has also been related to the overall eubacterial abundance in the analyzed system (1,5,32,42).…”
mentioning
confidence: 99%
“…These strains appeared to be related to the genus Agrobacterium, and thus it was unclear whether these strains (35). belonged to a previously undescribed Agrobacterium species or were in fact genuinely not Agrobacterium strains.…”
Section: Discussionmentioning
confidence: 99%
“…Two PCR assays were employed to demonstrate the presence of pRi in these strains, one targeted to the conserved virD2 gene (11) found in all pTi and pRi and one targeted to the T-DNA of pRi commonly associated with RMA crops (35). We have assumed that positive results in both of these assays and the subsequent results in the in vitro pathogenicity test indicate the presence of pRi in the nine ␣-Proteobacteria strains, although the presence of pRi was not demonstrated by other techniques, such as electrophoretic isolation of plasmids (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Suzaki et al, 2004) ;2) Ti プラスミド特異的プライマー (Cubero et al, 2006Haas et al, 1995;Picard et al, 1992;Pionnat et al, 1995;Pulawska and Sobiczewski, 2005;Puopolo et al, 2007;Sobiczewski et al, 2005) ;3)Ri プラスミド特異的プライマー (伊予住・市川,1999) ;4)特定の系統(オパイン型など) の病原性プラスミドのみを対象としたプライマー(Bini et al, 2008Dong et al, 1992;Eastwell et al, 1995;Kaufmann et al, 1996;Szegedi and Bottka, 2002;Tan et al, 2003;Weller and Stead, 2002;Yakabe et al, (Table 2) to determine which pathogenic plasmid respective strains carry and which pathogenic state they belong to. Amplification of the DNA fragments (780-784 bp) from the 16S rRNA gene (16S rDNA) (internal control) of the respective strains indicated that the respective PCR reactions were completed properly.…”
Section: Te Buffer 340unclassified